Agglomeration behaviour of titanium dioxide nanoparticles in river waters: A multi-method approach combining light scattering and field-flow fractionation techniques. (15th August 2015) - Chekli, L.; Roy, M.; Tijing, L.D.; Donner, E.; Lombi, E.; Shon, H.K.
Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are currently one of the most prolifically used nanomaterials, resulting in an increasing likelihood of release to the environment. This is of concern as the potential toxicity of TiO2 NPs has been investigated in several recent studies. Research into their fate and behaviour once entering the environment is urgently needed to support risk assessment and policy development. In this study, we used a multi-method approach combining light scattering and field-flow fractionation techniques to assess both the aggregation behaviour and aggregate structure of TiO2 NPs in different river waters. Results showed that both the aggregate size and surface-adsorbed dissolved organic matter (DOM) were strongly related to the initial DOM concentration of the tested waters (i.e. R 2 > 0.90) suggesting that aggregation of TiO2 NPs is controlled by the presence and concentration of DOM. The conformation of the formed aggregates was also found to be strongly related to the surface-adsorbed DOM (i.e. R 2 > 0.95) with increasing surface-adsorbed DOM leading to more compact structures. Finally, the concentration of TiO2 NPs remaining in the supernatant after sedimentation of the larger aggregates was found to decrease proportionally with both increasing IS and decreasing DOM concentration, resulting in more than 95% sedimentation in the highest IS sample. Graphical abstract: Highlights: Agglomeration and aggregate structure of TiO2 NPs in river waters was studied. A multi-method approach combining light scattering and FlFFF was employed. We observed a strong dependence of aggregate size with DOM of natural waters. DOM also played a significant role in aggregate structure.